Facilitative Mentorship: A Grounded Theory on Moderating Campus Organizations - Wilter Friales (JPAIR Institutional Research Journal)
Moderating students in the campus organizations is one of the significant faculty tasks being designated to manage student organizations. This study aims to establish a theory that explains how advising or moderating students in campus organizations is being done. This study utilized the Qualitative Grounded Theory approach using an in-depth interview with the seven participants, of which three are campus advisers, and four are student leaders. The interviews were transcribed, coded, and initial analysis was done to identify initial categories. The analysis of this research study consists of three phases- open, axial, and selective coding. In the open coding, the researcher examined the text for salient categories that emerged. Using constant comparative analysis, the researcher attempted to saturate the categories to identify the central or the core phenomenon. Facilitative mentorship emerged as the core category which characterized the mentoring of campus advisers. The researcher then engaged in axial coding in which the database was reviewed and collected new data to provide more substantial insights into specific coding categories that further explained the core category in which four categories emerged, namely Empowering and Enabling, Interactive and Open Communication, support, and affirmation and their guiding presence.